The role of bacterial urease activity on the uniformity of carbonate precipitation profiles of bio-treated coarse sand specimens - Charalampos Konstantinou (Nature Portfolio, 2021)
Abstract Protocols for microbially induced carbonate precipitation (MICP) have been extensively studied in the literature to optimise the process with regard to the amount of injected chemicals, the ratio of urea to calcium chloride, the method of injection and injection intervals, and the population of the bacteria, usually using fine- to medium-grained poorly graded sands. This study assesses the effect of varying urease activities, which have not been studied systematically, and population densities of the bacteria on the uniformity of cementation in very coarse sands (considered poor candidates for treatment). A procedure for producing bacteria with the desired urease activities was developed and qPCR tests were conducted to measure the counts of the RNA of the Ure-C genes. Sand biocementaton experiments followed, showing that slower rates of MICP reactions promote more effective and uniform cementation. Lowering urease activity, in particular, results in progressively more uniformly cemented samples and it is proven to be effective enough when its value is less than 10 mmol/L/h. The work presented highlights the importance of urease activity in controlling the quality and quantity of calcium carbonate cements.